Optical systems for diagnostics: Near-Infrared Imaging technique for detection of dental demineralisation - Salsone, Silvia; Versace, Carlo; Lombardo, Giuseppe; Zakian, Christian; Bartolino, Roberto (My University, 2012)
In dentistry, a correct detection of caries severity is still a challenging descision-making task that crucially a ects the choice for the best treatment plan. The challenge is to nd both the most objective parameters to detect caries at di erent stages (from an early reversibile stage to a severe one) and the most reliable method(s) that should be used to distinguish these stages. Currently, methods used in clinics are visual inspection, aided with light probe and pick inspection tools, and radiography. The main issue rising by the use of these methods is that both of them are subjective, with possibility for intra- and inter-examiner variability. For this reason, radiography needs an extreme care of interpretation especially when assessing occlusal caries. Visual methods, instead, are a ected by confounding factors, such as stain or uorosis, a ecting the accurate assessment of early caries lesions. Radiography, moreover, should be performed with care considering that the emission of ionising radiation may cause malignant change in tissues, especially for young age patients and are counter-indicated during pregnancy. They are also inadequate for the detection of initial caries and to locate the lesions looking at the superimposition of the tooth along its buccal-lingual axis. The aim of this study was to overcome the limits of the current detection techniques, o ering a non-invasive, objective method for the detection of caries at any stage of the demineralisation process. The proposed method measures the near-infrared (NIR) re ectance response of the tooth at three speci c wavelengths. It is then possible to investigate properties of the sample at the surface and in depth and get an image that maps the lesions on the occlusal view of the sample when combining these wavelengths. Due to the properties of the NIR light, this method is non-invasive, non-contact and allows for detection both at the enamel and at the dentine level. The NIR method o ers objective supporting information to quantify and detect dental caries and is especially suitable for areas a ected by confounding factors, such as stain. The objective of the study was to design and implement a NIR multispetral imaging system, developing e cient image analysis algorithms. In order to prove this objective, an in vitro validation of the technique against gold standard histology was performed together with a comparison to other detection methods - International Caries Detection and Assessment System (ICDAS - clinical visual inspection), bre optic transillumination method (FOTI - visual inspection with light probe), radiography and Quantitative Light-induced Fluorescence method (QLF), used in clinics or in research. A total of 112 teeh, molars and premolars, with di erent lesion severities were used for this study. Histologcal sections were obtained to con rm the lesion severities and used as a gold standard to compare the sensitivity and speci cty among techniques. Visual inspection methods recorded the highest values of sensitivity (ICDAS: >99%, FOTI: 93%) and speci city to dental caries (FOTI: >99%, ICDAS: 90%). However, these methods could have been highly facilitated by the in-vitro viewing of the samples. Sensitivity to dental caries was higher for NIR (91%) than for QLF (88%) and radiography (63%) while speci city was higher for radiography (81%) than for NIR (73%) and QLF (63%). The results from this study suggest that the NIR method has the ability to detect dental caries when other methods fail, providing an alternative to assist in the decision-making process with the further advantage of removing the confounding e ect of stain. This method can enhance patient communication and o ers an objective and safe alternative to ionising radiation methods.
Dottorato di Ricerca in Science and Technique of Mesophases and Molecular Materials, Bernardino Telesio, Cycle XXIV a.a. 2011-2012
Keywords: Fisica applicata; Sistemi ottici; Dispersione; Luce; Spettroscopia